Exploring the efficacy of an acceptance, mindfulness & compassionate-based group intervention for women struggling with their weight (Kg-Free): A randomized controlled trial. (1st May 2017) - Palmeira, Lara; Pinto-Gouveia, José; Cunha, Marina
Abstract: This randomized-controlled trial aims to test the efficacy of a group intervention (Kg-Free) for women with overweight or obesity based on mindfulness, ACT and compassion approaches. The intervention aimed to reduce weight self-stigma and unhealthy eating patterns and increase quality-of-life (QoL). Seventy-three women, aged between 18 and 55 years old, with BMI ≥25 without binge-eating seeking weight loss treatment were randomly assigned to intervention or control groups. Kg-Free comprises 10 weekly group sessions plus 2 booster fortnightly sessions, of 2h30 h each. The control group maintained Treatment as Usual (TAU). Data was collected at baseline and at the end of the Kg-Free intervention. Overall, participants enrolled in Kg-Free found the intervention to be very important and helpful when dealing with their weight-related unwanted internal experiences. Moreover, when compared with TAU, the Kg-Free group revealed a significant increased health-related QoL and physical exercise and a reduction of weight self-stigma, unhealthy eating behaviors, BMI, self-criticism, weight-related experiential avoidance and psychopathological symptoms at post-treatment. Results for self-compassion showed a trend towards significance, whereas no significant between-groups differences were found for mindfulness. Taken together, evidence was found for Kg-Free efficacy in reducing weight-related negative experiences and promoting healthy behaviors, psychological functioning, and QoL.